‘English for Religious Purposes’: integrating Islamic values and worldview into ELT materials - Preece, Abdul Shakour Duncan (2013)
The study set out to identify the important element and principles to be included in Islamized ELT materials. After this, the researcher designed a sample of Islamized materials (IM) which were implemented with a group of intermediate ESL learners at CELPAD, IIUM. The purpose of this was to evaluate the materials and gauge Muslim learners’ responses to them, in particular their perceptions of IM in terms of benefit for their English language. Overall, it can be concluded that combining cognitive, affective and religious content into IM, by means of thinking stories, has much to offer ELT. Comprehensive input and output in the form of discussions stimulated Muslim learners’ critical thinking skills and this, in turn, increased their intrinsic motivation to study English. The IM approach also offers learners practise in all four language skills in a holistic way.